Penerapan Digital Marketing sebagai Strategi Pemasaran untuk Meningkatkan Brand Awareness pada PT. Braja Inspired Indonesia - Fathur Rahman Maulana; Bayu Hari Prasojo (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of digital technology has encouraged tourism businesses to adapt their marketing strategies through the use of social media. TikTok has become one of the most widely used platforms due to its reliance on short video content with engaging visuals and its wide user reach. This community service activity aims to examine the application of digital marketing through the management of PT Braja Inspired Indonesia's TikTok account as an effort to support increased brand awareness. The method used was participatory mentoring, with the active involvement of participants and the company in the planning, production, publication, and evaluation of content. Data collection was conducted through direct observation, activity documentation, and analysis of TikTok account insights. The results of the activity indicate that planned content management, supported by video editing processes tailored to TikTok's characteristics and managed audience interactions, contributed to improved account performance. This improvement was demonstrated by increases in the number of views, profile visits, engagement levels, and follower growth during the management period. This suggests that TikTok has the potential to support increased brand awareness for PT Braja Inspired Indonesia through a planned digital marketing strategy oriented to the platform's characteristics.